2012
DOI: 10.7314/apjcp.2012.13.3.1003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between BMI, Body image, and Smoking in Korean Women as Determined by Urine Cotinine: Results of a Nationwide Survey

Abstract: Background: This study examined the influence of body mass index (BMI), subjective body perception (SBP), and the differences between BMI and SBP influence on smoking among women. Methods: This study used the Korea National Health and Nutrition Examination Survey IV-2, 3 2008−2009. A urinary cotinine test was administered to 5485 women at least 19 years of age. Individuals whose cotinine level was at least 50 ng/mL were categorized as smokers. A multiple logistic regression analysis was performed to estimate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…First, engagement in unhealthy behaviors such as smoking has been positively associated with delay discounting ( Story, Vlaev, Seymour, Darzi, & Dolan, 2014 ). Moreover, abstinence from smoking has shown to promote healthy behaviors such as having adequate dietary habits and taking exercise ( Jang et al, 2012 , Nagaya et al, 2007 ). Thus, the execution of these healthy behaviors associated with smoking abstinence might result in delay discounting decreases ( Bickel et al, 1999 , Secades-Villa et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, engagement in unhealthy behaviors such as smoking has been positively associated with delay discounting ( Story, Vlaev, Seymour, Darzi, & Dolan, 2014 ). Moreover, abstinence from smoking has shown to promote healthy behaviors such as having adequate dietary habits and taking exercise ( Jang et al, 2012 , Nagaya et al, 2007 ). Thus, the execution of these healthy behaviors associated with smoking abstinence might result in delay discounting decreases ( Bickel et al, 1999 , Secades-Villa et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using this method, past studies have revealed startling levels of underreporting in Korean females relative to males (Jung-Choi et al, 2012). And previous research has characterized the relationship between marital status, BMI, body image, and smoking in Korean women (Cho et al, 2008;Jang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Smoking rates for expectant mothers who were categorized as either underweight or overweight were higher than those of expectant mothers who were categorized as being of normal weight. In previous studies conducted in Japan and Korea, underweight women were more likely to smoke during pregnancy [ 24 , 25 ]. In addition, the proportion of overweight women classified as nonsmokers during the third trimester of pregnancy was lower than that of women of normal weight; however, the current smoking rate during early pregnancy was higher in overweight women relative to that of women of normal weight [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because there are numerous chemicals in cigarette smoke, the findings of this animal study could support our results from a biological perspective. Furthermore, women who subjectively perceived themselves as thin or fat were more likely to smoke [ 25 ], and weight concern was a major risk factor for smoking relapse after pregnancy [ 32 ]. Because maternal body dissatisfaction can influence their female children [ 33 ], it is possible that smoking mothers, particularly those who were underweight or overweight, influenced the weight of their children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation